Pembinaan Kelompok Wanita Tani dalam Inovasi Olahan Pangan Lokal Bersertifikat Halal di Kecamatan Rajabasa, Lampung - Wuryaningsih Dwi Sayekti; Rabiatul Adawiyah; Dyah Aring Hepiana Lestari; Yaktiworo Indriani; Tyas Sekartiara Syafani (Institut Pertanian Bogor, 2023)
The Women Farmers Group (KWT) is one of the farmer institutions in empowering women to support agricultural development programs. The target of the activity is KWT Harapan Kita, Sinar Harapan Village, Rajabasa Jaya Urban Village, Rajabasa Sub-District, Bandar Lampung City which has a productive business of processing food made from local food. Food processing made from local food raw materials is a strategic activity in accelerating food diversification in the community. This activity aims to increase the resource capacity of KWT Harapan Kita by increasing: 1) Knowledge of diversification of food and local food ingredients; 2) Knowledge and skills of local food processing; 3) Knowledge and skills of orderly administration and determination of product selling prices; and 4) Knowledge and understanding of the halal assurance system for products and halal certificate for KWT’s food products. The methods to be used are counseling, training, mentoring, and demonstrations. The results of the activity show that the knowledge and understanding of KWT Harapan Kita about local food diversification, orderly administration and determination of product selling prices, and halal certification of products has increased by 60,11%, and 20 types of local food processed products of KWT Harapan Kita got halal certification of LPPOM MUI with number 02100018190121. In the future, KWT Harapan Kita needs to be assisted to promote product development that has been carried out and certified so that the market opportunities will open and increase.